Effect of Early Life Stress on the Epigenetic Profiles in Depression - Li, Ming; Fu, Xiying; Xie, Wei; Guo, Wanxu; Li, Bingjin; Cui, Ranji; Yang, Wei (Frontiers in Cell and Developmental Biology, 2020)
Parallelly with some non-communicated diseases, depression, one of the most common mental dysregulations, has caused an increasing burden to the world health problem. Though experiments and clinical trials had been carried out, the mechanism of depression cannot be perfectly explained by unitary theory, and epigenetics may contribute to the dynamic alterations in depression. Moreover, early life stress, which is potentially granted to the susceptibility of depression acquisition during the following life, is evidenced-based precipitated in epigenetic changes of depression. Individuals and animals suffered from early life stress had the potential to develop depression, gained worse depressive symptoms, and resistant to depressants. Both clinical and preclinical studies assumed that early life stress-induced epigenetic changes of the HPA axis, monoamine, neuropeptides in DNA methylation, histone modification, and RNA transcriptions. Researches directly or indirectly indicated that epigenetic alterations followed by early life stress granted the depression. Of note, subtypes of early life stress, the timing of epigenetic status evaluated, demographic characteristics in humans, and strains traits in animals favored dynamic changes of the epigenetic profiles. Early life stress increased the risk of depression. Epigenetic alterations may add fuel to the fire in the process of depression occurring and blunt response to the antidepressants in the depressed with a history of early life stress. More researches needed to be done to investigate the direct evidences for early life stress-induced epigenetic changes to contribute to the vulnerability of depression.